Digitization and unemployment in South Africa: Preparing the youth towards taking advantage of 4IR - Ndou, Humbulani (University of the Witwatersrand, Johannesburg, 2023)
This study adopted a qualitative approach to assess the capabilities of South Africa toleverage the fourth industrial revolution (4IR) in addressing youth unemployment and thetransformative impact of 4IR on the socio-economic landscape. Through acomprehensive exploration of youth employment dynamics, education systems,infrastructure challenges, and the overarching development trajectory, the study providesnuanced insights into the opportunities and challenges posed by the rapid technologicaladvancements of the 4IR. The findings reveal a complex landscape, where concerns aboutjob displacement coexist with the promise of new employment opportunities andenhanced productivity. In the realm of education, the study highlights the urgency ofadapting South Africa's educational system to the demands of the 4IR. Outdated curriculaand inadequate preparation for future jobs underscore the need for a comprehensiveoverhaul, including the integration of technology at all levels and the development ofdigital literacy programs from primary education onwards. The digital divide betweenurban and rural areas emerges as a critical issue, necessitating infrastructure upgrades andpolicies to ensure widespread internet accessibility, particularly in underserved regions.This study recommends a multifaceted approach to address these challenges. Initiativesencompass comprehensive education system reforms, prioritizing digital literacy,infrastructure development, and widespread internet accessibility. The promotion ofentrepreneurship and youth development programs, strategic partnerships betweeneducational institutions and the private sector, and regulatory measures adapting to the4IR landscape are also proposed. Moreover, continuous skills development isrecommended to align the workforce skills with the evolving demands of the job market.This study offers a roadmap for South Africa's policymakers, educators, and stakeholdersto navigate the 4IR complexities, aiming to harness technological advancements whilemitigating challenges and fostering a resilient, innovative, and inclusive futur
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Fourth industrial revolution (4IR) i; Youth unemployment; Socio-economic landscape; Digitization and unemployment; UCTD; SDG-9: Industry, innovation and infrastructure